Population Dynamics of Whitefly on Cultivated Crops and its Management - Latif, M. A.; Akhter, N. (International Journal of Bio-resource and Stress Management, 2023)
Three experiments were carried out at the farm of Sher-e-Bangla Agricultural University during the period from February 2011 to May 2012 to know the population dynamics of whitefly on bush bean, okra and soybean, and to develop its management practices. Insecticides used for bush bean were bamper (imidacloprid) 20 SL, shobicron 425 EC, actara (thiamethoxam), chlorpyriphos 20 EC, sinothrin (cypermethrin) 10 EC, fortap (cartap) 50 SP; for okra, ripcord (cypermethrin), 5% tamarind fruit extract, 10% neem leaf extract, 10% bullock’s heart leaf extract, 10% dodder extract, 10% oleander leaf extract, 10%, dhutra leaf extract and 10% dholkolmi leaf extract; for soybean, marshal (carbosulfan) 20 EC, semcap (fenthoate), dursban (chlorpyriphos) 20 EC, basathrin (cypermethrin) 10 EC, fiter (λ-cyhalothrin) 2.5 EC, Shobicron 425 EC, Actara (Thiamethoxam) 25 WG. All three experiments were set in randomized complete block design (RCBD) and treatments were applied at 10 days interval. The population of whitefly was gradually increased with environmental temperature and humidity up to certain age of the cultivated crops then declined with increasing age of the crops. It was lower in okra than bush bean and soybean due to rainfall during the rainy season. All the chemical insecticides reduced the population of whitefly in bush bean and soybean, and increased their yields. In bush bean, imidacloprid showed the best performance by reducing 64.13% population of whitefly and increasing 66.00% yield of fresh fruits. The lowest population of whitefly (4.8 plant-1) and the highest fruit yield (4.92 t ha-1) were obtained by application of dhutra leaf extract on okra. Oleander leaf extract also gave the similar results against whitefly attacking okra and showed better performance than cypermethrin 10 EC in reducing whitefly population and increasing fruit yield.